2022
DOI: 10.1080/0886022x.2022.2081178
|View full text |Cite
|
Sign up to set email alerts
|

Lack or insufficient predialysis nephrology care worsens the outcomes in dialyzed patients – call for action

Abstract: The phenomenon of patients with advanced renal failure accepted for dialysis at a late stage in the disease process (late referral [LR]) is known almost from the beginning of dialysis therapy. It may also be associated with worse outcomes. The aim of the study was to assess the effect of referral time on the outcomes, such as number of hospitalizations, length of stay, kidney transplantation, and mortality. A study of 1303 patients with end-stage renal failure admitted for dialysis in the same period in Fresen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The long-term effects of nephrological care before dialysis on hospitalization after dialysis initiation have not been well described. A recent cohort study of incident dialysis patients demonstrated lower hospitalization frequencies in the early referral group only during the first nine months after dialysis initiation [ 18 ]. However, the follow-up time was truncated at 13 months, and allocation to the early or late referral groups was based only on the presence of a CDC at dialysis initiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The long-term effects of nephrological care before dialysis on hospitalization after dialysis initiation have not been well described. A recent cohort study of incident dialysis patients demonstrated lower hospitalization frequencies in the early referral group only during the first nine months after dialysis initiation [ 18 ]. However, the follow-up time was truncated at 13 months, and allocation to the early or late referral groups was based only on the presence of a CDC at dialysis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of referral to a nephrologist and the level of nephrological care impact on morbidity and mortality, as well as the quality of life [ 4–9 ]. Late referral is also associated with a poorer condition, increased costs, and increased morbidity and mortality after dialysis initiation [ 10 -– 18 ]. However, it has been questioned whether predialysis nephrological care per se impacts clinical outcomes after dialysis initiation, in addition to an optimal dialysis start [ 19–21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients' goals and preferences regarding treatment modality and access should be incorporated into the medical consultation 8‐10 . However, transitional care during the peridialysis period is inadequate and can result in an unplanned or emergency initiation of dialysis 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, transitional care during the peridialysis period is inadequate and can result in an unplanned or emergency initiation of dialysis. 11,12 Patient engagement is defined as the desire and capability to actively participate in care in a way uniquely appropriate to the individual, in collaboration with healthcare providers, to maximize outcomes and improve the experiences of care. 13 Patient engagement reflects the core value of person-centred care, in which patients are encouraged to be actively involved in processing information, making and acting on decisions and managing self-care.…”
Section: Introductionmentioning
confidence: 99%